Estimation of forest leaf area index and clumping index from the Global Positioning System (GPS) satellite carrier-to-noise-density ratio (C/N0). Issue 2 (1st February 2020) - Zhang, Yinghui; Fang, Hongliang; Ma, Li; Ye, Yongchang; Wang, Yao
ABSTRACT: Forest leaf area index (LAI) and clumping index (CI) are critical structural parameters to study the biomass, biogeochemical cycles, ecological simulation, and radiation transfer in a forest system. The ground-based measurements by traditional methods are costly, time-consuming, and are sensitive to variations in solar illumination conditions. Global Positioning System (GPS) satellites transfer L-band signals, and the presence of the forest canopy leads to an increase in noise. The GPS satellite's signal strength is generally described by the carrier-to-noise-density ratio ( C/N 0 ). This study explores the potential of using the GPS satellite C/N 0 to estimate forest canopy structural parameters. We performed experiments at 16 forest plots in northeastern China. LAI, CI, and canopy closure were estimated by digital hemispherical photography (DHP) using the CAN_EYE software. The GPS satellite C/N 0 was recorded with a modified smartphone application, GPSTest. The relationship between the forest canopy structural parameters and satellite C/N 0 was analyzed for those observations with satellite elevation angle (SEA) > 30°. The results show that both the true LAI and the effective LAI have strong linear and polynomial correlation with C/N 0 and the coefficient of determination ( R 2 ) is larger than 0.7. CI is linearly related to C/N 0 ( R 2 = 0.56). The linear relationship between the canopy closure and C/N 0 is much lower ( R 2 = 0.28). Accounting for the SEA effect, LAI can be estimated with R 2 > 0.8, and CI with R 2 = 0.6. LAI and CI can be well estimated from C/N 0 when the SEA effect is accounted for. In general, the GPS C/N 0 provides an alternative method to estimate forest canopy structural parameters.